1996
DOI: 10.1016/0022-1694(95)02907-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and modelling canopy water storage amounts in support of atmospheric deposition studies

Abstract: Monitoring and modelling rainfall interception and canopy wetness in support of acidification research Bouten, W.; Schaap, M.; Aerts, J.C.J.H.; Vermetten, A. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 14 publications
3
24
0
Order By: Relevance
“…These include the strain-gauge measurement of cantilever¯exing of branches under the load of intercepted water (Hancock and Crowther, 1979) and the attenuation of a microwave signal by water held on plant canopies lying in its path (e.g. Bouten et al, 1991Bouten et al, , 1996Wigneron et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These include the strain-gauge measurement of cantilever¯exing of branches under the load of intercepted water (Hancock and Crowther, 1979) and the attenuation of a microwave signal by water held on plant canopies lying in its path (e.g. Bouten et al, 1991Bouten et al, , 1996Wigneron et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Bouten et al, 1996). The difference between observed and predicted values of was lower than in previous applications of the Gash model in similar climatic conditions (Lankreijer et al, 1999).…”
Section: Rainfall Interceptionmentioning
confidence: 67%
“…During the 1990's research focused on the impact of air pollution on forest growth ('Aciforn project') at this site (Evers et al, 1991a). Several hydrological studies at that time found high interception losses (~40 %) from the forest (Tiktak and Bouten, 1994;Klaassen et al, 1998;Bouten et al, 1996), contributing to the debate about forest plantations in the centre of the Netherlands affecting the ground water recharge (Moors, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Grings et al (2009) have used radar remote sensing to explore the water storage of wetlands of the Paraná River Delta in Argentina. However, the remote sensing techniques and other relative techniques based on gamma-ray (Calder and Wright, 1986) and microwave attenuation (Bouten et al, 1996) are expensive to implement (Liu, 1998), although they are capable of monitoring the water level inside marshes on a regional scale (Bach and Mauser, 2003). Bradley (2002) used the MODFLOW to simulate the annual water table dynamics of a flood plain with a large amount of weekly data.…”
mentioning
confidence: 99%